Intercultural Communication (Study On Students Of 17 August 1945 Jakarta University In The Independent Student Exchange Program 2) - Biantoro, Nadia Menik Monica; Agustin, Dinar Ayu Chandra (UNIVERSITAS PAKUAN, 2022)
Independent Campus (MBKM) is one of the policies made by the Ministry of Education and Culture with the aim of supporting the success and quality of students. One of the MBKM programs that provides the opportunity to study outside the home campus and can take cross-study courses for one semester is the Independent Student Exchange (PMM). The purpose of this study is to find out how the process of adaptation to intercultural communication and how to overcome Culture Shock was carried out by students at the University of August 17, 1945 Jakarta in participating in the PMM 2 Program. The research method used was descriptive qualitative. The research subjects were three students from the 17 August 1945 University of Jakarta who took part in PMM at Hasanuddin University, Medan State University, and Mataram University. Data collection methods using interviews and documentation. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The results of this study are that the adaptation process in the dormitory and campus environment has obstacles such as the local community who are less able to mingle and limit themselves. However, this only happened at the beginning of the meeting. Then, in terms of culture, there are no significant difficulties, it's just that the food is not in accordance with what is usually consumed. Then in communicating, the obstacles are in the differences in language, accent, and vocabulary meanings from each region. Of all the obstacles and efforts made, the way students can adapt to a new environment and overcome Culture Shock is not much different, namely by being open, accepting cultural differences, learning to understand the character and style of community communication, and being directly involved in all forms of activities. culture in that area.